Definition of in situ pavement instrumentation for data collection to develop a pavement performance model - Salini, Reus (2008)
After the implementation of the AASHTO Road Test many researches have been carried out regarding material and pavement performance, both in laboratory and in situ. Many methods for pavement evaluation and design were obtained based on empirical or empirical-mechanistic approaches. Nowadays these methods are used in pavement analysis and design supported by a set of shift factors which consider the variables not included in their definition. At the present time, the development of economical electronic sensors has made possible a successful full-scale instrumentation of pavements. This paper focuses on the problems and solutions related to instrumentation and its integration in the research of pavements in situ to collect relevant data for pavement modelling. The instrumentation includes monitoring environmental conditions (rainfall, air temperature, solar radiation, UV radiation and wind), pavement state (temperature, moisture and groundwater level), pavement response (displacement, tensile and compression strains, shear effects, deformations and pressures) and vehicle characteristics (classification, axle configuration, tyre types and pressures, speed, weight by axle at high speed and the driving transversal shift, i.e. the wheel distance from the pavement border). The definition of the instrumentation for pavement response was based on conventional pavement analysis using numerical modelling in which the sensors position was chosen to ensure reliable measurements. The external parameters evaluation, such as the vehicle classification, where the contact area and the tyre pattern are included, was considered by sample-collection.